Dilithium Tetrachlorocuprate(II) Catalyzed Oxidative Homocoupling of Functionalized Grignard Reagents - Hua, Si-Kai; Hu, Qiu-Peng; Ren, Jiangmeng; Zeng, Bu-Bing (Synthesis, 2013)
An efficient procedure is described for the oxidative homocoupling of functionalized Grignard reagents using a catalytic amount of dilithium tetrachlorocuprate(II) (CuLi2Cl4) in the presence of pure oxygen gas. This method is applied successfully to a variety of aryl, heteroaryl, alkyl, alkenyl and alkynyl halides, which are converted into the corresponding homocoupled products in good to excellent yields.
Keywords: homocoupling; dilithium tetrachlorocuprate(II); Grignard reagents; oxidant; metalation